In vivo validation of a mechanically adaptive microfluidic intracortical device as a platform for sustained local drug delivery - Kim, Youjoung; Druschel, Lindsey N.; Mueller, Natalie; Sarno, Danielle; Gisser, Kaela; Hess-Dunning, Allison; Capadona, Jeffrey R. (Frontiers in Biomaterials Science, 2023)
Intracortical microelectrodes (IME) are vital to properly functioning brain-computer interfacing (BCI). However, the recording electrodes have shown a steady decline in performance after implantation, mainly due to chronic inflammation. Compliant materials have been explored to decrease differential strain resulting in lower neural inflammation. We have previously developed a fabrication method for creating mechanically adaptive microfluidic probes made of a cellulose nanocrystal (CNC) polymer nanocomposite material that can become compliant after implantation. Here, we hypothesized that our device would have a similar tissue response to the industry standard, allowing drug delivery therapeutics to improve neural inflammation in the future. RNA expression analysis was performed to determine the extent of neural inflammation and oxidative stress in response to the device compared to controls and to naïve shame tissue. Results presented for both four- and eight-weeks post-implantations suggest that our device offers a promising platform technology that can be used to deliver therapeutic strategies to improve IME performance.